ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS BERDASARKAN TEORI APOS DITINJAU DARI SELF EFFICACY SISWA - Ashri, Dewi Nadhila; Khaerunnisa, Etika (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2022)
This study aims to find out the ability to solve mathematical problems based on APOS theory when examined by a student's self efficacy. Studies are conducted in class X Accountability SMK Nurul Huda Baros Kabupaten Serang that has of 28 students. The research subjects were 6 students consisting of two students from each category of self-efficacy. The study uses a type of qualitative research with a descriptive method. Data collection techniques in this study used questionnaires, tests, and interviews that a questionnaire instrument in the form of statements about self efficacy and a test consisting of two question problems solving of quadratic equations. Studies have revealed that students with a high self efficacy has the ability to solve mathematical problems to the stage of the scheme, the student with moderate self efficacy has the ability to solve problems to the stage of objects, while the student with low self efficacy has the ability to solve problems only until the stage of action